2017
DOI: 10.1371/journal.pone.0186622
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of SMO-1, the SUMO homolog in Caenorhabditis elegans

Abstract: SUMO proteins are important post-translational modifiers involved in multiple cellular pathways in eukaryotes, especially during the different developmental stages in multicellular organisms. The nematode C. elegans is a well known model system for studying metazoan development and has a single SUMO homolog, SMO-1. Interestingly, SMO-1 modification is linked to embryogenesis and development in the nematode. However, high-resolution information about SMO-1 and the mechanism of its conjugation is lacking. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In mammals, SUMO-2, unlike SUMO-1, can assemble poly-SUMO chains on different substrates in the same protein. For SMO-1, such poly-SUMO chain formation has not been reported in vivo, although poly-SMO-1 chains were observed in-vitro (Surana et al, 2017). These poly-SUMO chains were implicated in recruiting other proteins to give rise to more complex interactions (Psakhye et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In mammals, SUMO-2, unlike SUMO-1, can assemble poly-SUMO chains on different substrates in the same protein. For SMO-1, such poly-SUMO chain formation has not been reported in vivo, although poly-SMO-1 chains were observed in-vitro (Surana et al, 2017). These poly-SUMO chains were implicated in recruiting other proteins to give rise to more complex interactions (Psakhye et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…These enzymes consist of an E1 (AOS-1/UBA-2), an E2 (UBC-9), several E3 ligases . Unlike vertebrates and some plants, C. elegans expresses only a single SUMO protein, SMO-1 (Surana et al, 2017). In mammals, SUMO-2, unlike SUMO-1, can assemble poly-SUMO chains on different substrates in the same protein.…”
Section: Introductionmentioning
confidence: 99%
“…Examination on the genes in this cluster found that the elevation of certain genes could repress the variant formation in C. elegans . For example, SMO family genes play important role in repairing DNA damage, 54 SMO‐1 modification on the ubiquitin E3 HERC2 triggers recruitment of further repair factors at DNA repair foci, including the ubiquitin E3 BRCA1/BARD1 55 ; POS‐1 has an important role in regulating the expression of maternal mRNAs in germline blastomeres, and mutations in pos‐1 cause several defects in the development of the germline blastomeres 56 ; PUF RNA‐binding proteins (RNABPs), PUF‐3/11 and PUF‐5/6/7, control different specific aspects of oocyte formation: silencing PUF‐3/‐11 via RNAi yielded an embryonic lethal phenotype, 57 whereas depletion of PUF‐5 and PUF‐6/7 together caused defects in oocyte formation and early embryonic cell divisions 58 . Our results suggest that DNA damage might occur in the reproduction system of C. elegans during bacterial infection.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to a lack of extensive characterization of conformational flexibility of native‐state in SUMO systems. Native‐state landscape of ubiquitin has been explored both by experimental as well as computational means, but only a few such reports are available in case of SUMO proteins …”
Section: Introductionmentioning
confidence: 99%
“…Nativestate landscape of ubiquitin has been explored both by experimental as well as computational means, [31][32][33] but only a few such reports are available in case of SUMO proteins. 30,[34][35][36] A flexible native-state can be crucial for functionality of proteins, 37,38 especially in cases where a single protein tackles multiple substrates single handedly, for example, SUMO protein in drosophila. 4 Conformational flexibility in any protein emanates from its excursion to low energy excited states, also called "near-native states," where its structure is slightly different from that of the native state.…”
mentioning
confidence: 99%